The Returns to Education in Italy: A New Look at the Evidence - Claudio Lucifora; Simona Comi; Giorgio Brunello (Institute for the Study of Labor (IZA), 2000)
The purpose of this paper is to provide an update of the empirical evidence on the private returns to education in Italy. First, we show that, whilst returns to education in Italy (based on gross wages) are in line with the European average, educational attainment is generally much lower (particularly at secondary and tertiary levels). How can we reconcile these findings? Based on a simple human capital model - where the optimal level of schooling is given by equating the marginal return to the marginal cost of education – we speculate that either marginal costs are steeper in Italy or that a larger share of the population involved in human capital investment faces high marginal costs in Italy compared to the European average. Second, we examine whether the estimated returns to education have varied significantly over time. The evidence is that returns have not changed much over the period 1977 to 1995, with the exception of 1993 and 1995, when they have increased significantly, especially among female employees. Quite interestingly, the observed increase in the returns to education has been almost completely driven by higher returns to education in the public sector. Assuming that skill biased technical change has been an important factor in shifting out the marginal returns to education, an important question for future research is why these shifts have only affected returns in the public sector of the economy. Third and last, we confirm the usual finding in the international literature that accounting for measurement error in years of schooling and/or for the endogeneity of educational choices by using instrumental variables significantly increases the returns to education with respect to estimates based on OLS methods. We also show that adding family background variables to the set of instruments significantly increases returns, which suggests that these variables affect mainly the subgroup of individuals with higher marginal returns to schooling.
Keywords: J24; J31; I21; I22; 330; Education; earnings; Bildungsertrag; Bildungsinvestition; Bildungswesen; Schätzung; Italien